Odpowiedzi

Najlepsza Odpowiedź!
2009-09-12T17:42:07+02:00
A. ²/₇ - 3⅛ × 2,4 = ²/₇ - 15/2 = 4/14 - 105/14 = 101/14

b. - 1,6 ÷ 3¹¹/₁₅ + 1³/₁₄ = -16/10:56/15+17/14 = -16/10*15/56+17/14 = -6/14+17/14 = 11/14

c. ( 0,3 + ⅘ ) ÷ ( 6¹/₁₅ - ⅔ ) = (3/10+8/10):(91/15-10/15) = (11/10):(81/15) = (11/10)*(15/81) = 33/162

d. - 2,4 - 3,6 × ( 1⅜ ÷ 3,3 - ⁵/₉ ) = -6*(11/8:33/10-5/9) = -6*(11/8*10/33-5/9) = -6*(5/12-5/9) = -6* (45/108-60/108) = -6*(-15/108) = 15/18

e. 1,6 - ⅔ / 1,6 × ⅔ = 16/10-⅔:16/10*⅔ = 16/10-10/24*⅔ = 16/10-10/36 = 576/360-100/360 = 476/360 = 1 176/360 = 1 22/45

f. 4,8 / 1¹/₁₅ - 2¼ / 5,4 = 48/10*15/16 - 9/4*10/54 = 9/2-5/12 = 54/12 - 5/12=49/12=4 1/12
2009-09-12T18:19:20+02:00
W przykładzie a brakuje na końcu minusa :
a. ²/₇ - 3⅛ × 2,4 = ²/₇ - 15/2 = 4/14 - 105/14 = -101/14


2009-09-12T19:37:15+02:00